2016
DOI: 10.1371/journal.pone.0165992
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus sydowii and Other Potential Fungal Pathogens in Gorgonian Octocorals of the Ecuadorian Pacific

Abstract: Emerging fungal diseases are threatening ecosystems and have increased in recent decades. In corals, the prevalence and consequences of these infections have also increased in frequency and severity. Coral reefs are affected by an emerging fungal disease named aspergillosis, caused by Aspergillus sydowii. This disease and its pathogen have been reported along the Caribbean and Pacific coasts of Colombia. Despite this, an important number of coral reefs worldwide have not been investigated for the presence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 41 publications
0
37
0
Order By: Relevance
“…They reported the incidence of aspergillosis, an emerging fungal disease caused by A. sydowii in gorgonian corals ( G. ventalina and G. flaballum ) in the Caribbean. Soler-Hurtado et al (2016) also reported this disease in gorgonian corals ( Leptogorgia obscura and L. sp.)…”
Section: Fungal Diseases Of Coralsmentioning
confidence: 87%
See 4 more Smart Citations
“…They reported the incidence of aspergillosis, an emerging fungal disease caused by A. sydowii in gorgonian corals ( G. ventalina and G. flaballum ) in the Caribbean. Soler-Hurtado et al (2016) also reported this disease in gorgonian corals ( Leptogorgia obscura and L. sp.)…”
Section: Fungal Diseases Of Coralsmentioning
confidence: 87%
“…However, Toledo-Hernández et al (2008) stated that they doubted that A. sydowii is the only fungus that can cause aspergillosis in G. ventalina because it is not always present in diseased corals. Soler-Hurtado et al (2016) found A. sydowii and other potential fungal pathogens in gorgonian octocorals of Ecuador (see below). Since A. sydowii can be present in healthy corals, perhaps environmental factors are involved as well.…”
Section: Fungal Diseases Of Coralsmentioning
confidence: 99%
See 3 more Smart Citations